Organizing and running duathlon competitions in Ukraine - Водлозеров, Владимир (Slobozhanskyi Herald of Science and Sport, 2017)
Vladimir Vodlozerov Purpose: to analyze the system of organizing and running competitions for a variety of continuous triathlon in Ukraine for compliance with the rules of the International Federation of Triathlon. Material & Methods: based on the study of the specialized literature, the regulatory framework of the triathlon federation, a comparative analysis of the organization and conduct of competitions between the duathletes in the world and in Ukraine carried out. Results: it’s revealed a discrepancy between the length of the segments of the greater part of the combined distances at which classification competitions are held in Ukraine, the official formats of international duathlon competitions in Europe and the world. Conclusion: recommendation on elimination of discrepancies of the Ukrainian formats of the distances influencing efficiency of the competitive process in duathlon are proposed.